The function and mechanism of action of uterine microecology in pregnancy immunity and its complications - Shen, Liping; Wang, Weiwei; Hou, Weiwei; Jiang, Chenfei; Yuan, Yi; Hu, Liqing; Shang, Anquan (Frontiers in Cellular and Infection Microbiology, 2023)
The human microbiota influences physiology, disease, and metabolic reproduction. The origin of uterine bacteria is controversial. The main assumption is that the germs enter the uterine cavity from the vagina through the cervical canal, bloodstream, fallopian tubes, and gynecological surgical channels. Understanding the microbiota at various anatomical sites is critical to the female reproductive system and pregnancy. Today’s study focuses on the role of uterine bacteria in pregnancy and embryo implantation. According to our findings, the uterine microbiome influences embryo implantation and pregnancy outcome. Pregnancy is a natural, evolutionarily selected approach to human reproduction. During pregnancy, the microbiota of the reproductive tract changes, facilitating the maintenance of pregnancy, and the human immune system undergoes a series of changes that recognize and adapt to the non-self. From the beginning of pregnancy, a non-self fetus must establish a placenta of embryonic origin to protect itself and promote growth; the VMB tends to be more stable and lactobacillus-dominated in late gestation than in early gestation. Any material that disrupts this connection, such as microbial changes, is associated with a higher risk of poor health and poor pregnancy outcomes in women (eclampsia). The presence of any material that disrupts this connection, such as microbial changes, is associated with a higher risk of poor health and poor pregnancy outcomes (preeclampsia, preterm birth, gestational diabetes, etc.). In this work, we review the last decade of relevant research to improve our understanding of the mechanisms by which the microbiota of the female reproductive tract influences female reproductive health. This work discusses the mechanisms associated with the reproductive tract microbiota and pregnancy immunity, as well as the impact of an abnormal microbiota on adverse pregnancy outcomes. Emphasis is placed on the characteristics and sources of the female vaginal, uterine, and placental microbiota and the importance of a well-stabilized local human microbiota and immune system for embryo implantation, placental development, fetal growth, and pregnancy outcome.